2015
DOI: 10.3382/ps/pev216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oligosaccharides extract from palm kernel expeller on growth performance, gut microbiota and immune response in broiler chickens

Abstract: This study examined the prebiotic effects of oligosaccharides extract from palm kernel expeller (OligoPKE) on growth performance, cecal microbiota and immune response of broiler chickens. A total of ninety 1-day-old broiler chicks (Cobb-500) were randomly allocated to three treatment groups of six pens (replicates) with five birds per pen. Dietary treatments were: (i) basal diet as control, (ii) basal diet plus 0.5% OligoPKE, and (iii) basal diet plus 1% OligoPKE. Birds growth traits (ADG, ADFI and G:F) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 32 publications
2
37
1
Order By: Relevance
“…Previous studies have focused on the addition of supplemental enzymes, yeast and other probiotics and, depending on the study, some beneficial effects were found (Dhama et al, 2015;Rezaei et al, 2015;Alefzadeh et al, 2016). In the current study, the numbers of aerobic, lactic acid-producing, and coliform bacteria did not differ (P >0.05) among experimental groups, demonstrating the safety of adding OM to both animal and human populations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have focused on the addition of supplemental enzymes, yeast and other probiotics and, depending on the study, some beneficial effects were found (Dhama et al, 2015;Rezaei et al, 2015;Alefzadeh et al, 2016). In the current study, the numbers of aerobic, lactic acid-producing, and coliform bacteria did not differ (P >0.05) among experimental groups, demonstrating the safety of adding OM to both animal and human populations.…”
Section: Resultsmentioning
confidence: 99%
“…Oligosaccharides were extracted from raw palm kernel expeller (PKE) using water (without enzyme) as solvent, following the procedure of Rezaei et al (2015). Briefly, 1 L distilled water was added to 200 g ground PKE in a one-litre Scott bottle, shaken for 1 hour at room temperature, and later autoclaved.…”
Section: Methodsmentioning
confidence: 99%
“…While MOS does not have the GRAS status, animal trials with MOS supplementation at a dose of 1% (10 mg/mL) showed no adverse effect [42,43]. Likewise, no adverse effects were observed in in vivo trials when oligosaccharides from PKC at a concentration of 10 mg/mL were used as supplements [44,45].…”
Section: Salmonella Enteritidis Adherence Inhibition To Caco-2 Cellsmentioning
confidence: 99%